MULTILINGUALISM IN SOCIAL MEDIA: INDONESIAN K-POP FANS LANGUAGE CHOICES ON TWITTER - Fathimah Azzahrah; Yusnita Febrianti; Nurenzia Yannuar; Evynurul L. Zen (Ma Chung Press, 2022)
This research paper aims to identify multilingualism and language choice by looking at types of code-switching and code-mixing techniques practiced by Indonesian K-Pop fans on Twitter. Also, it examines the rationales and functions of such practice, especially as it is done in Indonesian context. Two data collection methods are used in this research. First, data were taken from several Indonesian K-pop fanbase accounts on Twitter from September 2020 to May 2021. Additionally, we also obtained data through an open-ended questionnaire participated by Indonesian K-pop fans. Our research shows that Indonesian K-Pop fans frequently implement code-switching and code-mixing techniques by combining Indonesian, English, Korean, and Japanese into their tweets. Words, phrases, and clauses from multiple languages are used. The results also show that fans practice code- switching and code-mixing in order to project a more globalized impression, create a friendly conversation, synchronize perceptions, boost language skills, and form identity.